2020
DOI: 10.1007/s00125-020-05274-6
|View full text |Cite
|
Sign up to set email alerts
|

The joint association of diabetes distress and depressive symptoms with all-cause mortality in Japanese individuals with type 2 diabetes: a prospective cohort study (Diabetes Distress and Care Registry in Tenri [DDCRT 20])

Abstract: Aims/hypothesis The independent association of depressive symptoms and diabetes distress with mortality risk in individuals with diabetes has not been evaluated. We examined the temporal joint association of diabetes distress and depressive symptoms at baseline and the subsequent risk of all-cause mortality. Methods The longitudinal data of 3118 individuals with type 2 diabetes were obtained from a large Japanese diabetes registry. To assess the joint association of diabetes distress and depressive symptoms at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…Our study found, in agreement with previous studies, that women, young patients, and those with low education reported worse general health [ 19 , 42 46 ], high diabetes-related distress [ 37 , 47 53 ] and low confidence in diabetes self-management [ 54 , 55 ]. Physiological and lifestyle factors, including diet and physical activity, may contribute to the gender and educational differences [ 46 , 55 , 56 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our study found, in agreement with previous studies, that women, young patients, and those with low education reported worse general health [ 19 , 42 46 ], high diabetes-related distress [ 37 , 47 53 ] and low confidence in diabetes self-management [ 54 , 55 ]. Physiological and lifestyle factors, including diet and physical activity, may contribute to the gender and educational differences [ 46 , 55 , 56 ].…”
Section: Discussionsupporting
confidence: 93%
“…This is in line with previous studies [ 47 , 49 , 65 ] that focused, as this study does, on recently diagnosed patients. While others have shown that poor glycemic control was associated with high diabetes-related distress [ 37 , 51 , 52 , 66 68 ], most of these studies included patients with a long-standing diabetes. Thus it would be interesting to test whether the associations are modified by diabetes duration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is consistent with a previous study conducted in diabetic patients, indicating that patients with psychological distress (measured by Mental Health Inventory 5) were at increased risk of all-cause mortality and CVD events. 15 Another study found a 1.76-fold higher risk of mortality and a 1.69-fold higher incidence of CVD events with psychological distress in participants with vs those without diabetes. 38 Psychological distress is already acknowledged as an important risk factor for CVD events.…”
Section: Discussionmentioning
confidence: 97%
“… 8–12 Women with diabetes have a higher risk of psychological problems than men, particularly in those taking non-insulin glucose-lowering drugs for treatment. 13 However, other studies 14 , 15 have reported an association between psychological distress and increased all-cause mortality in men, but not in women, and participants’ age ≥65 years. 16 Although studies have shown an association between psychological distress and increased mortality, it is unclear whether the association differs in participants with and without diabetes.…”
Section: Introductionmentioning
confidence: 95%